"The Narrative Synthesis of Human Frailty and the Social Attributes of the Singaporean Society in Philip Jeyaretnam’s Abraham’s Promise" - Ali Mhoodar , Rana ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This paper explores the issue of human frailty in Philip Jeyaretnam’s Abraham’s Promise (1995). It attempts to emonstrate how human frailty is synthesized by three inextricable factors, namely, disappointment, family disintegration, and loss of idealism. Therefore, the study analyzes the novel’s protagonist weakness as an indication of human frailty that exemplifies a collective representation of the Singaporean social life. It follows a qualitative methodology of the selected novel’s characters and narrative structure. Therefore, the discussion of disappointment is reinforced by interpreting the protagonist’ feelings of despondency. Furthermore, it highlights family disintegration and loss of idealism as crucial factors of human frailty depicted in the novel. As such, the study unravels these social impasses via identifying the Singaporean society portrayed through Jeyaretnam’s fictional setting. Thus, the study’s theoretical side is enhanced by scrutinizing the narrative attributes of the Singaporean settings and characters.